An objective assessment of the co-ordination of fiscal policies among CARICOM countries - Williams, Gladwin B. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1999)
Seeks to show that integrated fiscal policies is one of the most important strategies necessary to foster regional integration among CARICOM countries.